Longer shared parental leave is associated with longer duration of breastfeeding: a cross-sectional study among Swedish mothers and their partners - Maria Grandahl; Jenny Stern; Eva-Lotta Funkquist (BMC, 2020)
Abstract Background Breastfeeding is associated with health benefits for both the mother and infant and is therefore important to support; moreover, parental leave is a beneficial factor for breastfeeding. The Swedish parental leave is generous, allowing each parent to take 90 days; additionally, a further 300 days can be taken by either parent. Generally, mothers take 70% of the parental leave days, mainly during the first year. However, breastfeeding duration has declined in the last decade, and it is not known how shared parental leave is associated with the duration of breastfeeding. Aim To investigate how parental leave is associated with the duration of exclusive and partial breastfeeding of the infant during the first 12 months after birth. An additional aim was to describe infants' and parents' characteristics and mode of birth in association with the duration of exclusive and partial breastfeeding. Methods This cross-sectional study was part of the Swedish Pregnancy Planning Study, conducted in Sweden in 2012-2015. The parents were recruited at 153 antenatal clinics in nine counties. In total, 813 couples completed a follow-up questionnaire 1 year after birth. Linear regression models were used to analyse the association between parental leave and the duration of breastfeeding. Results Infants were exclusively breastfed for, on average, 2.5 months (range 0-12 months) and partially breastfed, on average, 7 months (range 0-12 months). Most of the parental leave was taken by the mother (mean = 10.9 months) during the infant's first 12 months, while the partner took 3 months, on average. The parental leave (used and planned) during the infant's first 24 months were, on average, 21 months. In the multivariate linear regression analysis, mothers' and partners' high level of education (p < 0.001, p = 0.044, respectively), mothers' higher age (p = 0.049), non-instrumental vaginal birth (p = 0.004) and longer parental leave for the first 24 months (p < 0.001) were associated with longer duration of partial breastfeeding. Conclusion The duration of partial breastfeeding was associated with higher parental educational level, higher age, non-instrumental vaginal birth and longer parental leave.